DEVELOPMENT OF RISK ASSESSMENT METHODS IN THE IMPLEMENTATION OF EXPLORATION PROJECTS - R. R. Imamov (Стратегические решения и риск-менеджмент, 2024)
The peculiarity of oil and gas projects is their long implementation period, during which they are subject to the influence of a large number of different risk factors that complicate project implementation and result in failure to achieve the planned economic indicators set by investors. The effective operation of companies therefore depends on how reliably investors can predict the prospects for project development. The success of the subsequent functioning of the investment project depends to a large extent on the reliability of the assessment of the effectiveness of the investment project, based on the optimally chosen strategy of its development, and, above all, on the anticipation of possible risk factors and tools for their prevention. Therefore, at present, the competitive struggle in the oil and gas production industry is currently shifting to the area of pre-project preparation of investment projects and increasing the reliability (quality) of their economic efficiency assessment at the stage of making a decision to start their implementation.Geological risks become important in the implementation of exploration projects, the first stage in the overall process of developing the Company's assets.  It is necessary to find a balance between the cost of project implementation and the amount of accumulated hydrocarbons for the forecast period, which will ensure maximum profitability of the project. The challenge to optimize the financial outlay on the implementation of geological exploration works by focusing on the most promising and important projects for companies becomes relevant. In this regard, the article considers the methodological approaches proposed by the author to assess the risks of exploration with the aim of improving the efficiency of the planning process and reducing inefficient financial costs.